Viral Envelope Membrane: A Special Entry Pathway and a Promising Drug Target - Palombi, Nastasja; Brai, Annalaura; Gerace, Martina; Di Maria, Salvatore; Orofino, Francesco; Corelli, Federico (Current Medicinal Chemistry, 2021)
Enveloped viruses belong to a large class of pathogens responsible for multiple serious diseases. Their spread into new territories has been the cause of major epidemics throughout human history, including the Spanish flu in 1918 and the latest COVID-19 pandemic. Thanks to their outer membrane, consisting essentially of host lipids, enveloped viruses are more resistant to enzymes and are also less susceptible to host immune defenses than their naked counterparts. Therefore, the development of effective approaches to combat enveloped virus infections represents a major challenge for antiviral therapy in the current century. This review focuses on the characteristics of enveloped viruses, their importance in the entry phase, drugs targeting envelope membrane- mediated entry, and those specifically designed to target the envelope. The broad- -spectrum antiviral activity of these compounds can be attributed to their ability to affect the envelope, an essential structural feature common to several viruses. This makes this class of compounds agents of great interest when no specific drugs or vaccines are available to block viral infections.
Keywords: virus